Candidate genes for performance in horses, including monocarboxylate transporters - Regatieri, Inaê Cristina [UNESP] (2017)
Some horse breeds are highly selected for athletic activities. The athletic potential ofeach animal can be measured by its performance in sports. High athletic performance depends on the animal capacity to produce energy through aerobic and anaerobic metabolicpathways, among other factors. Transmembrane proteins called monocarboxylate transporters, mainly the isoform 1 (MCT1) and its ancillary protein CD147, can help the organismto adapt to physiological stress caused by physical exercise, transporting lactate and H+ ions. Horse breeds are selected for different purposes so we might expect differences in the amount of those proteins and in the genotypic frequencies for genes that play a significant role in the performance of the animals. The study of MCT1 and CD147 gene polymorphisms,which can affect the formation of the proteins and transport of lactate and H+, can provide enough information to be used for selection of athletic horses increasingly resistant tointense exercise. Two other candidate genes, the PDK4 and DMRT3, have been associated with athletic potential and indicated as possible markers for performance in horses. Theoxidation of fatty acids is highly effective in generating ATP and is controlled by the expression of PDK4 (pyruvate dehydrogenase kinase, isozyme 4) in skeletal muscle during and after exercise. The doublesex and mab-3 related transcription factor 3 (DMRT3) gene encodes animportant transcription factor in the setting of spinal cord circuits controlling movement invertebrates and may be associated with gait performance in horses. This review describeshow the monocarboxylate transporters work during physical exercise in athletic horses and the influence of polymorphisms in candidate genes for athletic performance in horses.